Efficacy of echolaser smart interface-guided laser ablation in volume reduction of symptomatic benign thyroid nodules - Malik, Iftikhar; Mitchell, Janeil; Thomas, Johnson (Frontiers in Endocrinology, 2024)
The management of benign symptomatic thyroid nodules until recent years has been limited to surgery, radioactive iodine treatment, or surveillance which is associated with the burden of morbidity of complications or symptom non-relief as well as cost. Laser ablation has emerged as a minimally invasive alternative, this uses laser energy to thermally ablate nodule tissue, leading to volume reduction and symptom relief. Long-term treatment response data is growing but remains limited in the United States. Our study aims to quantify the effectiveness of laser ablation in reducing the volume of thyroid nodules over a 12 to 18-month period.Retrospective review of data was conducted for 63 adults with cytologically benign, solid symptomatic thyroid nodules ranging from 1.333 cm 3 to 103.794 cm 3 in volume. Ultrasoundguided laser thermal ablation was performed on all nodules using EchoLaser X4 Smart Interface device with 1084 nm diode laser to deliver total ablation energy (joules), calculated per device guidelines. Serial sonographic volume measurements were conducted 1 month, 3 -6 months, 6 -12 months, and 12 to 18 months post-ablation intervals.Study cohort was comprised of 63 thyroid nodules. reduction in nodule volume increased progressively over time, with median reductions of 46.05% [STD 21.8] at 1 month, 60.33% [STD 20.1] at 3-6 months, 68.69% [STD 18.8] at 6-12 months, and 64.04% [STD 19.27] at 12-18 months. A total of 62, 56, 42, and 17 nodules had available data for analysis at these respective intervals.This study demonstrated a marked progressive reduction of thyroid nodule volume following ablation. The treatment appears to be consistently effective in reducing symptoms across a wide range of nodule sizes, although the degree of volume reduction varies. The results of our study underscore the potential of laser ablation as a viable treatment option for thyroid nodules, with a sustained reduction in nodule volume observed over an extended post-procedure period.